2013
DOI: 10.18554/2317-1154v2n1p32
|View full text |Cite
|
Sign up to set email alerts
|

Comparação Das Características Sociodemográficas De Saúde E Qualidade De Vida De Idosos Rurais Segundo Sexo

Abstract: Objetivou-se comparar as características sociodemográficas, econômicas, de saúde e a qualidade de vida (QV) de idosos residentes na zona rural segundo o sexo. Trata-se de inquérito domiciliar e transversal. Foram entrevistados 850 idosos no domicílio com os instrumentos: parte do Questionário Brasileiro de Avaliação Funcional Multidimensional, World Health Organization Quality of Life-BREF e World Health Organization Quality of Life Assessment for Older Adults. Utilizaram-se os testes qui quadrado e t-Student … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In our study, more than half of the sample (57.5%) did not live in the same city where the reference hospital was located. The literature also provides data on high prevalence of UI in rural areas of Brazil [7][8][9]. To attend face-to-face appointments, these patients would have costs regarding transport and other expenses related to the time away from home, such as food.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, more than half of the sample (57.5%) did not live in the same city where the reference hospital was located. The literature also provides data on high prevalence of UI in rural areas of Brazil [7][8][9]. To attend face-to-face appointments, these patients would have costs regarding transport and other expenses related to the time away from home, such as food.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary incontinence (UI) is the most common pelvic floor disorder (PFD) affecting approximately 26% of adult female population in developing countries [1]. In Brazil, the prevalence is also high [2][3][4][5][6], and studies have indicated that 15 to 40% of Brazilians in rural areas suffer from UI [7][8][9]. This highlights the necessity for establishing treatment resources targeting populations in remote regions, within which telehealth emerges as a viable consideration.…”
Section: Introductionmentioning
confidence: 99%